2003
DOI: 10.1128/aac.47.9.3012-3014.2003
|View full text |Cite
|
Sign up to set email alerts
|

Postantibiotic Effects of Daptomycin against 14 Staphylococcal and Pneumococcal Clinical Isolates

Abstract: Daptomycin mean staphylococcal postantibiotic effects (PAEs) were 1.1 to 6.2 h, with a mean of 2.5 h. The mean pneumococcal PAEs were 1.7 h, ranging between 1.0 and 2.5 h. The staphylococcal and pneumococcal postantibiotic sub-MIC effects at 0.4 times the MIC ranged from 3.0 to >12.0 h and 1.9 to >12.0 h, respectively.The postantibiotic effect (PAE) is a pharmacodynamic parameter contributing to the choosing of antibiotic dosing regimens. It is defined as the length of time that bacterial growth is suppressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 15 publications
3
10
0
Order By: Relevance
“…Other observed microbiological properties of MX-2401 include the low frequency of spontaneous resistance, the low potential for emergence of resistance, and a long in vitro PAE, consistent with bacterial cell damage during exposure that impacts the growth fitness of bacteria. The PAE of MX-2401 was similar to or slightly longer than those of vancomycin and daptomycin as reported in our study and in keeping with literature values for the latter two antibiotics (7,21). The long PAE was also observed in in vivo studies (9).…”
supporting
confidence: 78%
“…Other observed microbiological properties of MX-2401 include the low frequency of spontaneous resistance, the low potential for emergence of resistance, and a long in vitro PAE, consistent with bacterial cell damage during exposure that impacts the growth fitness of bacteria. The PAE of MX-2401 was similar to or slightly longer than those of vancomycin and daptomycin as reported in our study and in keeping with literature values for the latter two antibiotics (7,21). The long PAE was also observed in in vivo studies (9).…”
supporting
confidence: 78%
“…The effect of subinhibitory drug levels following suprainhibitory levels which persist between dosing intervals is referred to as the postantibiotic sub-MIC effect (PA-SME). Staphylococcal PA-SME effects at 0.4 times the MIC ranged from 3.0 h to 1 12 h [17] . PA-SMEs and PAEs for S. aureus and Enterococcus faecalis were dosedependent, and it was concluded that the relatively high PA-SME and PAE values found in vitro support oncedaily dosing of daptomycin [17,18] .…”
Section: Chemistry and Mode Of Actionmentioning
confidence: 99%
“…Daptomycin staphylococcal PAE ranged from approximately 1.1 to 6.2 h, with a mean of 2.5 h [17,18] . The effect of subinhibitory drug levels following suprainhibitory levels which persist between dosing intervals is referred to as the postantibiotic sub-MIC effect (PA-SME).…”
Section: Chemistry and Mode Of Actionmentioning
confidence: 99%
“…Daptomycin MIC 90 values are typically 0.25-0.5, 1, and 0.25 mg/L for Staphylococci spp., vancomycin-susceptible Enterococci spp., and group B Streptococci spp., respectively (Sader et al 2005 ). Daptomycin also exhibits a prolonged and dose-dependent PAEs (from 1.1 to 6.2 h against S. aureus and in the 1 to 2.5 h range against S. pneumoniae ) (Hanberger et al 1991 ;Safdar et al 2004 ;Pankuch et al 2003 ). Unfortunately, the ability of these PD parameters to predict clinical effi cacy is limited since they do not take into account any interactions of the drug or its penetration at the site of infection.…”
Section: In Vitro and In Vivo Assessment Of Daptomycin Pd Parametersmentioning
confidence: 95%